# How do I show that the sum $(a+\frac12)^n+(b+\frac12)^n$ is an integer for only finitely many $n$?

Show that if $a$ and $b$ are positive integers, then $$\left(a +\frac12\right)^n + \left(b+\frac{1}{2}\right)^n$$is an integer for only finitely many positive integers $n$.

I tried hard but nothing seems to work. :(

• Do you know the binomial theorem? What happens when you expand these two terms out? – tomcuchta Apr 30 '12 at 19:29
• @tomcuchta Yes, I do. $$2C_0 + 2C_1 (a+b) + \ldots + 2^n(a^n + b^n) = 2^nk, \quad k\in \mathbb{Z^{+}}$$But I can't think of anything after this. – MSC Apr 30 '12 at 19:32
• Your expansion, involving $a^n$ makes me wonder if you have written what you want in the problem. But if you have, it seems that when that quantity is an integer, then $4(b + \frac 12)^n = \frac {2b+1}{2^{n-2}}$ is also. – mike Apr 30 '12 at 19:53
• @mike I am sorry, it was a typo. It's supposed to be $\left(a+\frac12\right)^n$. – MSC Apr 30 '12 at 20:37
• If $a=2^p - 1$ and $b = 2^p$, $$\left(a +\frac12\right)^{q} + \left(b+\frac{1}{2}\right)^{q}= \text{Integer}$$ If $a=2^q - 1$ and $b = 2^q$, $$\left(a +\frac12\right)^{p} + \left(b+\frac{1}{2}\right)^{p}= \text{Integer}$$ where $p =2m + 1,\; q =2m - 1$, for all integer $m>0$. Just for info. – Tito Piezas III Jan 14 '18 at 7:12

## 6 Answers

First of all, rewrite the equation as others have, to yield $(2a+1)^n+(2b+1)^n = m\cdot 2^n$, or in other words $(2a+1)^n+(2b+1)^n \equiv 0\pmod {2^n}$. Now, if $n=2k$ is even then for the equation to hold $\bmod 2^{2k}$ it must certainly hold $\bmod 4$; i.e., $\bigl((2a+1)^k\bigr)^2 + \bigl((2b+1)^k\bigr)^2\equiv 0\pmod 4$. But this can't work, because both of the squares on the left must be congruent to $1 \bmod 4$ and so their sum is congruent to $2$. Therefore, $n$ must be odd, say $n=2k+1$.

Now, the left side can be factored using the classic formula for $\frac{x^n-y^n}{x-y}$ (substitute $x=2a+1, y=-(2b+1)$), yielding $$(2a+1)^{2k+1}+(2b+1)^{2k+1} = (2a+2b+2)\cdot(x^{2k}+x^{2k-1}y+x^{2k-2}y^2+\cdots+y^{2k})$$ But the factor on the right is odd (it's the sum of $2k+1$ terms each of which is odd), so for the LHS to be $0\bmod 2^n$, we must have $2a+2b+2\equiv 0 \pmod {2^n}$, and this can only be true for finitely many $n$; it becomes impossible as soon as $2^n\gt 2a+2b+2$.

• This (rqna.net/qna/mymyn-number-theory-problem.html) is same by the same author – lab bhattacharjee Aug 10 '13 at 3:44
• @labbhattacharjee Actually, that appears to be a direct clone of math.SE - I would suggest reporting the site to the StackExchange administrators for stealing content (I believe there's a standardized link for doing so). – Steven Stadnicki Aug 10 '13 at 8:00

Hint $\$ Suppose that $\rm\:\left(\dfrac{2a+1}{2}\right)^2 + \left(\dfrac{2b+1}{2}\right)^n = m\in \mathbb Z.\:$ Then scaling by $\rm\:2^n\:$ we deduce

$$\rm 2^{n-2}(2a+1)^2 + (2b+1)^n =\, m\, 2^n$$

which yields a contradiction if $\rm\:n > 2\!:\:$ LHS = even + odd = odd, but RHS is even.

• Both power are n - you wrote the first as 2. – marty cohen Jan 5 '15 at 23:07
• @marty That was the original version of the question (see also Brian's answer). – Bill Dubuque Jan 5 '15 at 23:22
• Looks like the OP changed it so both exponents are n. I also get upset when I solve a problem only to find that the OP has changed it by the time I submit my solution. – marty cohen Jan 5 '15 at 23:57

There are much more elegant ways to prove the result, but here's a quasi-experimental approach that shows how you might attack such a problem. (And it actually proves that there are no positive integers $n$ for which the sum is an integer.)

First note that $\left(a+\frac12\right)^2=a^2+a+\frac14$ is always $\frac14$ more than an integer. Thus, $$\left(a +\frac12\right)^2 + \left(b+\frac{1}{2}\right)^n$$ is an integer if and only if $\left(b+\frac12\right)^n$ is $\frac14$ less than an integer, i.e., if and only if there is an integer $m$ such that $\left(b+\frac12\right)^n=m-\frac14$. If this is the case, then $4\left(b+\frac12\right)^n=4m-1$.

1. Is this possible when $n=1$? No: $4\left(b+\frac12\right)^1=4b+2$ is an integer, but it's an even integer, and $4m-1$ is odd.

2. What if $n=2$? Still no: $4\left(b+\frac12\right)^2=4b^2+4b+1=4(b^2+b)+1$, which is odd, but it's one more than a multiple of $4$, and $4m-1$ is one less than a multiple of $4$.

3. For $n=3$ matters are still worse: $4\left(b+\frac12\right)^3=4b^3+6b^2+3b+\frac12$, which isn't even an integer.

4. For $n=4$ we have $4\left(b+\frac12\right)^4=4b^4+8b^3+6b^2+2b+\frac14$, which is worse yet.

Now look at the constant terms in (1)-(4): $2,1,\frac12$, and $\frac14$. They should suggest the conjecture that the constant term in $4\left(b+\frac12\right)^n$ is $\dfrac1{2^{n-2}}$. If you can prove this, you're practically done. Equivalently, try to prove the

Conjecture: The constant term in $\left(b+\frac12\right)^n$ is $\dfrac1{2^n}$.

If you already know the binomial theorem, you can get this immediately from it. Otherwise, you can prove the conjecture by induction on $n$.

Note that $$\left(a+\frac{1}{2}\right)^n + \left(b+\frac{1}{2}\right)^n=\frac{1}{2^n}\left(c^n+d^n\right),$$ where $c=2a+1$ and $d=2b+1$.

Let $2^e$ be the highest power of $2$ that divides $c+d$.

If $n$ is even, the highest power of $2$ that divides $c^n+d^n$ is $2$.

For odd $n$, note that $u^n+v^n=(u+v)(u^{n-1}+u^{n-2}v+\cdots +v^{n-1})$. The second term in this product is odd. It follows that the highest power of $2$ that divides $c^n+d^n$ is $2^e$.

Thus if $n\gt e$, then $\left(a+\frac{1}{2}\right)^n + \left(b+\frac{1}{2}\right)^n$ is not an integer.

• If $n=1$ then there are lots of solutions. Beyond that I was going to say "work mod 4" which I think is the same idea. – Mark Bennet Apr 30 '12 at 20:49
• Sorry - the question changed between your answer and my comment. – Mark Bennet Apr 30 '12 at 20:50

Notice that $$\left(a+\frac12\right)^n+\left(b+\frac12\right)^n=\left((2a+1)^n+(2b+1)^n\right)/2^n$$ and use the binomial theorem to expand.

The problem is equivalent to the following:

Let $q\in\mathbb{Q}^{+}$ with $\nu_2(q)=0$. Prove that $\nu_2(q^n+1)\geq n$ for only finitely many $n$.

Proof. If $2|n$ then $\nu_2(q^n+1)\leq 1$. Now choose odd $n$ large enough so that $||q+1||<2^n$ where $||\frac{a}{b}||=|a|+|b|$. Then $v_2(q^n+1)=v_2(q+1)+v_2\left(\sum_0^{n-1} (-q)^i\right)=v_2(q+1)<n$.

Hence only finitely many solutions exist.

Explanation of my reformulation: By rearrangement, the initial equation is $(2a+1)^n+(2b+1)^n\in 2^n \mathbb{Z}$. The pair $(2a+1,2b+1)$ is equivalent to specifying a $q\in\mathbb{Q}^{+}$ with $\nu_2(q)=0$, because we can make $(2a+1,2b+1)\to\frac{2a+1}{2b+1}$ and likewise map $q=\frac{m}{n}\to(m,n)$ with $m,n$ relatively prime. Then the condition is just saying $\nu_2(q^n+1)\geq n$.